2021
DOI: 10.1080/1747423x.2021.1928310
|View full text |Cite
|
Sign up to set email alerts
|

Multi-scale fallow land dynamics in a water-scarce basin of the U.S. Southwest

Abstract: Improving our understanding of land-use change is critical for water management in semi-arid areas, due to its effects on the hydrological cycle. In the U.S. Southwest, fallowing farmland has become one strategy to reduce water use. Previous to this study, the magnitude and location of changes in fallowing have not been studied in depth. Using the 30-meter Cropland Data Layer, this study assessed the spatial and temporal patterns of fallowing in the U.S. portion of the Rio Grande/Río Bravo Basin (RGB) at three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Fallowing farmland is a conservation method that may result in large volumes of water conservation within a short period of time, which either reduces water use or reallocates conserved water for other uses (Plassin et al, 2021). Studies have shown land fallow has signi cant importance in land reclamation, national food security, encouraging environmental improvements and making sure the usage of land is sustainable (Qing & Hualin, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fallowing farmland is a conservation method that may result in large volumes of water conservation within a short period of time, which either reduces water use or reallocates conserved water for other uses (Plassin et al, 2021). Studies have shown land fallow has signi cant importance in land reclamation, national food security, encouraging environmental improvements and making sure the usage of land is sustainable (Qing & Hualin, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…California water system includes the Central Valley Project (CVP), the State Water Project (SWP), the Los Angeles Aqueduct (LAA), and the Colorado River Aqueduct (CRA). Water in California is Across the world, institutions such as federal governments and water providers have established programs to in uence farmer decisions and change farming practices; such programs are often started to achieve product control to increase fallen commodity prices, to improve the environment and water quality, to restore soil fertility, and/or to conserve water for future use (Ferris & Siikamäki, 2009;Plassin et al, 2021). In the Southwest region of the United States, farmers are compelled to fallow irrigated elds, permanently or temporarily, for four reasons: i) reallocating scarce water resources to reduce farmland acreage and cultivate higher value crops; ii) serving as an alternative to more expensive and less exible water-saving practices and technologies, such as irrigation system enhancements or crop shifting; iii) accommodating water rights transfers from agricultural to urban uses; and iv) receiving nancial compensation in exchange for enhancing water conservation, contributing to improved environmental ows or reservoir levels, recharging aquifers, or meeting other demands (Plassin et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Given the persistent issue of ongoing water scarcity and the rise in water demands unrelated to irrigation, the concept of land fallowing, which involves intentionally leaving land uncultivated for one or multiple growing seasons [13], has emerged as a potential strategy for curbing agricultural water consumption in the U.S. Southwest [14]. Plassin et al [15] analyzed four primary approaches to land fallowing in the U.S. Southwest. One of them is initiatives for conservation that have been introduced to encourage farmers to willingly cease agricultural cultivation on land, whether for a temporary or permanent duration [16], which is applied in the states, including Colorado and California [17].…”
Section: Introductionmentioning
confidence: 99%
“…A number of states in the Southwest are considering various options to encourage the fallowing of agricultural lands as a response to water scarcity [8]. This paper evaluates the economic merit of growing guar (Cyamopsis tetragonoloba L.) as an alternative forage replacement crop during drought-induced water restrictions, especially in relation to the needs of the dairy industry.…”
Section: Introductionmentioning
confidence: 99%